Sedimentology and evaporite genesis of Neogene continental Sabkha Playa complex, Karakecili Basin, central Anatolia, Turkey - Türkmen, I; Özkul, M (Northeastern Science Foundation Inc, 1999)
The Karakecili basin is an intermontane basin located about 60 km SE of Ankara in central Turkey and covers an area of approximately 200 km(2). This Neogene basin is bordered by granite and gabbro of the Kinsehir massif to the north-northeast and east, and massive gypsum of the Mezgit Formation (Oligocene) to the west and southwest. Facies associations characterizing a playa complex crop out in this Neogene basin These facies associations include, from the basin margin to the center, I-Red massive conglomerate and pebbly mudstone (alluvial fan), 2-Organicaliy rich mudstone, bearing sparse gypsum crystals (marsh), 3-Cross-laminated-bedded gypsarenite (eolian), 4-Brown-gray mudstone bearing gypsum-roses and discoidal and radial gypsum crystals (saline mudflat), and 5-Bedded-laminated gypsum (ephemeral salt lake). Evaporites occur commonly as discoidal crystals, sigmoidal crystals, rosettes, and nodular forms. These were formed displacively within mudstone from calcium sulphate - rich groundwater during the arid conditions. Stratified gypsum represented by macrocrystalline aspects is generally restricted laterally and is precipitated by the evaporation of brine sheets on mudflats. The source of evaporites in the Karakecili basin is the gypsum of the Oligocene Mezgit Formation.
Keywords: Tectonic Controls; Sedimentation; Sequence; Deposits; Lake